Optimization study of water cooled PV system - Yip, Wei Hao (2020)
This project demonstrates a method to optimize a water cooled PV system by means of software simulation to obtain the best design and then construction of the design. The average power for both cooled panel and uncooled panel were 75.15W and 73.0575W respectively which leads to a 2.864% power increase. The cooled panel had an average efficiency of 10.545% while the uncooled one was 10.41%.